In Influencers We Trust: How TikTok Content Shapes Gen Z’s Brand Awareness and Buying Intention - Jocelline Aarona Putricia; Dewi Mustikasari Immanuel (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The rapid growth of influencer marketing on social media has made it an important digital marketing strategy, especially on TikTok. However, empirical evidence regarding the role of influencer credibility in shaping Generation Z’s buying behaviour in Indonesia remains limited. This study aimed to analyze the effect of influencer credibility on brand awareness, brand trust, and buying intention among Indonesian Generation Z TikTok users, as well as to examine the moderating role of gender. A quantitative survey method was employed using purposive sampling, and an online questionnaire was distributed to 138 Indonesian Generation Z TikTok users. The collected data were analyzed using PLS-SEM. The results showed that influencer credibility positively influenced brand awareness, brand trust, and buying intention, with brand awareness serving as an effective mediator between influencer credibility and buying intention, while brand trust did not, indicating that cognitive familiarity through brand awareness is more influential than emotional trust in driving Generation Z’s buying intentions on TikTok. Gender differences did not moderate the relationship between brand trust and buying intention, indicating similar behavioral tendencies across males and females. The findings offer new empirical insights into Generation Z’s buying behavior on TikTok and practical implications for marketers in developing influencer strategies that emphasize brand awareness to stimulate buying intentions.